Feasibility and acceptability of a videoconference-based cognitive-behavioral intervention for caregivers of individuals living with mild cognitive impairment or early Alzheimer's disease - Phylicia Verreault; Marie-Christine Ouellet; Céline Mavounza; Robert Jr Laforce; Jean Vézina; Carol Hudon (PEC Innovation)
Objective: The objective of the current pilot study was to investigate the feasibility and acceptability of a videoconference-based cognitive behavioral (CBT) intervention for caregivers of individuals living with mild cognitive impairment or early Alzheimer's disease. The intervention included psychoeducation on emotions, strategies for management of unhelpful emotions and thoughts, behavioral activation, breathing and relaxation, strategies for communication and information on external resources. Methods: This study used a cross-sectional design with two groups of four caregivers who received an 8-week CBT-based intervention via videoconference. Measures of feasibility and acceptability were collected post-intervention as well as suggestions for improvements. Results: Eight female caregivers were enrolled in the intervention, one participant opted out at the seventh session. Of those who completed the program, all participants reported that it was very easy to participate using the online modality. All participants felt that the intervention was at least partly adapted to their experience and needs as a caregiver. Five out of seven participants (71%) indicated that they felt better and would recommend the intervention to another caregiver. Conclusion: The current study demonstrated that it is feasible and acceptable to use a videoconference CBT-based group intervention with MCI or mild AD female caregivers. Innovation: This is the first videoconference-based cognitive behavioral intervention for caregivers of individuals living with MCI or mild AD.